Sikap Mahkamah Konstitusi Mengenai Keberlakuan Perjanjian Internasional dalam Hubungannya dengan Hukum Nasional - Gede Marhaendra Wija Atmaja; Nyoman Mas Aryani; Anak Agung Sri Utari; Ni Made Ari Yuliartini Griadhi (Jurnal Magister Hukum Udayana, 2018)
The purpose of this study is to find out the position of the Constitutional Court which later? an understanding of the politic of International agreement law adopted by the Republic of Indonesia. This can be reviewed from the legal considerations that underlying the Constitutional Court Decision. It is a legal research that examines the laws and regulation related to Constitutional Court through several stages: elaborate textual studies, completing textual studies, analyzing legal materials and determine conclusions. The study shows that International and legalized agreement that has not been ratified are placed as part of national law and are used as a reference to enrich the reasoning horizon in interpreting the constitution. Law on the ratification of the International Agreement containing norms which are attachments and an inseparable part of the law, which in its existence as a law constitutes the authority of the Constitutional Court to examine its constitutionality. In this context, the constitutional Court embraced the politic law of monism with the primate of national law and the Constitutional Court embraced the politic law of dualism when examining the constitutionality of the law concerning the ratification of the International Agreement-in terms of subject matter.